Repair and retrofitting of damaged columns under seismic loading - Lim, Kar Er (2017)
As one of the most critical structural element of an infrastructure, the column pose a great danger when it is exposed to sudden and critical loadings that are caused by natural disaster such as an earthquake. Failure of the column could lead to the collapse of the infrastructure, eventually leading to loss of lives. This project is carried out to explore various repair and retrofitting methods that could be employed to restore the strength and stability of the columns after it has been damaged seismically. This would minimize cost as compared to tearing down the infrastructure and rebuilding it. In this project, 2 short columns are first being damaged seismically with the use of machinery that simulates the horizontal force that it would be exposed to, during an earthquake. The columns would be loaded to failure, observing the horizontal displacement closely. The vertical loadings are held constant to simulate real life situation, in which the loading it takes vertically remains unchanged. Following, the cracks of the columns would be repaired before being strengthened by the different methods explored in this report. Columns with damaged reinforcements would not be repaired as this report explores the possibility of repairing concrete strength. However, due to limitations of time allowance, schemes were not tested. In contrary, the presumption on the results of the schemes was carefully analyzed to draw a conclusion from the designed schemes.